The mummyfesto - Green, Linda (London : Quercus, 2013)
When Sam, Jackie and Anna successfully campaign to save their children's school lollipop lady, they are asked by a TV reporter if they fancy standing in the general election. It is, of course, a crazy idea: Sam's youngest son has an incurable disease, Jackie is desperate for another child and her mum is struggling with Alzheimers, Anna's teenagers - and marriage - are in danger of going off the rails. But sometimes the craziest ideas turn out to be the best. And just think what they could do if they got to run the country .
Keywords: Women -- Political activity -- Fiction; Working mothers -- Fiction; Domestic fiction